Optimalisasi Penggunaan Teknologi Augmented Reality di Era Digital pada Sekolah Dasar - Aprilia, Yesinta Dewi; Suwandayani, Beti Istanti; Kuncahyono, Kuncahyono (Jayapangus Press, 2025)
This study aims to analyze the strategy of optimizing the use of Augmented Reality (AR) technology in the digital era in elementary schools. Augmented Reality is a technology that unites the real world with the virtual world through smartphones, thus enabling a more interactive and immersive learning experience. Augmented Reality (AR) technology in education allows students to visualize the concept of learning materials that are difficult to understand. This research identifies the implementation of Augmented Reality technology in the learning process. The incorporation of virtual and real elements not only makes learning material more interesting, but also makes it easier for learners to understand and remember. The research methodology used is qualitative with data collection through observation, interviews and documentation. Data analysis uses the Miles and Huberman data analysis model. Fieldresult show that the implementation of ugmented Reality technology in the learning process helps visualize learning materials and makes learning more interesting, so that students are enthusiastic in the learning process. In the implementation of Augmented Reality technology, of course, there are obstacles that become obstacles to the learning process, the obstacles include lack of device storage, unstable internet networks, and limited encyclopedia books for scanning. To overcome these obstacles, strategies are needed to optimize the use of Augmented Reality technology, including teacher training, providing sufficient space on the device, network stability, ad adequate encyclopedias.